Answer: {g,h}={−3,−4}
Explanation:
System of Linear Equations entered :
[1] 6g-2h=-10
[2] 11=h-5g
Equations Simplified or Rearranged
[1] 6g - 2h = -10
[2] 5g - h = -11
// Solve equation [2] for the variable h
[2] h = 5g + 11
// Plug this in for variable h in equation [1]
[1] 6g - 2•(5g+11) = -10
[1] -4g = 12
// Solve equation [1] for the variable g
[1] 4g = - 12
[1] g = - 3
// By now we know this much :
g = -3
h = 5g+11
// Use the g value to solve for h
h = 5(-3)+11 = -4
and your solution is
{g,h} = {-3,-4}